THU0511 Macrophage Growth by Polyploidization in Chronic Inflammation. (10th June 2014) - Triantafyllopoulou, A.; Nanda, I.; Haaf, T.; Henneke, P.; Voll, R.
Abstract : Background: How macrophages grow at sites of chronic inflammation is not well understood. In rheumatoid arthritis and several granulomatous autoimmune diseases, such as sarcoidosis, giant cell arteriitis and granulomatosis with polyangiitis, macrophages are thought to increase their size by cell to cell fusion thus producing multinucleated giant cells and osteoclasts. However, the underlying molecular and cellular programs for multinucleation and cell growth of macrophages at sites of chronic inflammation remain unclear. Objectives: In this study, we aimed to elucidate the mechanisms of macrophage growth in the presence of proinflammatory cytokines in vitro and in a microbial model of chronic granulomatous inflammation in vivo. Methods: We stimulated mouse bone marrow- derived macrophages with TNF in vitro and examined macrophage growth, cell cycle and ploidy using long term live cell imaging, image cytometry, molecular biological approaches and cytogenetics. To examine macrophage growth in a TNF-rich granulomatous environment in vivo, we injected mice i.p. with Mycobacterium bovis BCG and examined macrophage size and ploidy in liver granulomas using immunofluorescence and image cytometry. Results: We show that the proinflammatory cytokine TNF can induce macrophage growth by polyploidization producing giant cells which contain nuclei with increased DNA content. Using long term live cell imaging, we found that polyploid macrophages can be generated by cytokinesis failure due to supernumerary centrosomes and DNA trapped at the cleavage furrow. TNF regulated cell cycle events by modulating the expression of cell cycle proteins and promoting the proliferation and survival of polyploid rather than diploid macrophages. Conclusions: TNF can induce macrophage polyploidization by regulating the cell cycle and promoting cytokinesis failure. This pathway of macrophage polyploidization is distinct from the previously described macrophage polyploidization by cell to cell fusion which is not known to require cell cycle regulation. We propose that macrophage polyploidization by TNF-modulated cell cycle regulation may be an important mechanism for the growth and survival of macrophages in chronic inflammatory diseases. Acknowledgements: Funding: Federal Ministry for Education and Research, Germany and Marie Curie FP7 International Reintegration Grant. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2468